Insulin-Related Skin Lipohypertrophy in Type Two Diabetes: A Clinical Study of a Case Series, with Ultrasonographic and Histopathologic Implications - Sandro Gentile; Felice Strollo; Giuseppina Guarino; Andrea Ronchi; Ersilia Satta; Teresa Della-Corte; Elisabetta Fulgione; Graziella Babino; Edi Mattera; Emilia Martedì; Roberta Di Martino; Raffaella Fiorentino; et al. (Diabetology)
Introduction: The most frequent local complication of insulin injection is the occurrence of subcutaneous nodules due to incorrect injection technique. Injection into nodules negatively impacts metabolic compensation and the requirement for greater insulin doses due to its partial and erratic absorption. Despite these concepts being accepted by the scientific community, it is not yet clear whether injection into nodules is causally related to worsening chronic diabetes (DM) complications and the morphological nature of such nodules. Aim: This multicenter study aimed to evaluate the associations between structural characteristics of skin nodules and chronic DM complications. A secondary endpoint was to evaluate the histological structure of those nodules, looking for differences between lipohypertrophies (LH) and amyloid nodules (LIDA). Methods: For this purpose, 816 DM patients with LH and 1033 without LH underwent a clinical and ultrasound study comparing metabolic data, injection habits, and frequency of complications. Excisional biopsies of the skin nodules were performed in a small series of eight subjects. Results: Data observed confirm a strong relationship between LH and diabetes chronic complications other than poor glycemic control. Histology of biopsies from the skin nodules showed mild foreign-body-like inflammation, prevailing mega-adipocytes (65%), apoptosis, and fibrosis but could not detect any amyloid fibrils. In four cases, intra-nodular fluid was present with an insulin concentration several times higher than in blood. Conclusions: We confirmed LHs to be significantly associated with insulin administration errors, duration of insulin therapy, greater daily doses and duration of insulin administration, and the presence of micro- and macro-vascular DM complications. LH nodules displayed no typical morphological features and were indistinguishable from LIDA nodules with which they shared several histologic similarities, albeit within the frame of a general picture of LIDA inhomogeneity. Further targeted studies are warranted to clarify the remaining doubts.